Study on Flood Risk Transfer Mechanisms in the Pearl River Basin - TANG Meng; HE Li; YIN Chuang; LIU Jia (Renmin Zhujiang)
For the Pearl River Basin, in order to study the decay/amplification effect of themulti-risk source transfer process, and to identify the temporal and spatial evolutioncharacteristics and transfer mechanisms of flood risk, based on the four-factor theory ofdisasters, this paper selects 11 indexes with an overall consideration of disaster-inducingfactors, hazard-inducing environment, hazard-bearing body and hazard prevention and mitigationcapabilities, constructs an assessment model of flood risk, and builds a Markov chain risktransfer model by GIS technology to study the spatial and temporal evolution and transfermechanisms of flood risk in the Pearl River Basin. The results show that: ① The main factorscausing flood risk in the Pearl River Basin are heavy precipitation and typhoon, followed bypopulation, economy, etc. ② In time, the flood risk is high in flood years, and is low in dryyears. In space, the high risk area is located in the downstream, and the low risk area is locatedin the upstream. The overall trend is higher in the east than in the west. ③ The probability ofcross-level transfer of flood risk in the same water resources area of the Pearl River in the sameyear is small. In the water resources areas with adjacency water system, the flood risk has thefeatures of both enhanced transfer and attenuated transfer. The flood risk will not be transferredby crossing level.